ANALISIS SISTEM INFORMASI EKSEKUTIF PEMASARAN UNTUK MENDUKUNG STRATEGI PEMASARAN PADA RSIA HERMINA DAAN MOGOT - Hendra Putra (Jurnal Manajemen FE-UB, 2013)
Problems Identified in this study are : (1) How does the internal environment RSIA Hermina Daan Mogot ? ; (2) How External environment RSIA Hermina Daan Mogot ? (3) How to formulate a marketing strategy on RSIA Hermina Daan Mogot ? ; (4) How does the syatem marketing information on RSIA Hermina Daan Mogot ?. Hermina Daan Mogot RSIA hospital that specialized in maternal and child health. In support of its activities, marketing strategy is needed which can be used as a guide for hospitals to implement marketing activities. Therefore, it is important for hospitals to find out how internal and external environment influences companies to produce the correct marketing strategy for the company. Methodology in carrying out the author traveled through one step method. Method of descriptive method with a type study examples on RSIA Hermina Daan Mogot. The study was conducted on the basis of a survey by interviewing and questionnaires for staff and management at the secondary and higher. When analyzing data matrix Aids CRM/EFAS, SWOT diagrams, internal-external matrix and SWOT matrix. On the basis of the analysis was done, the alternative strategies that should be run hospital consolidation strategy. This strategy can be realized by increasing advertising in the media more effectively. To support this strategy, the authors analyze the marketing executive information systems. This system is expected to need Executive reporting in the form of charts and tables that have been completed at the site expand and drill through can be met, so that managers can get the data and information as possible in accordance with their needs.